Heat transfer enhancement of spray cooling by copper micromesh surface. (November 2022) - Hu, Yongyan; Lei, Yifan; Liu, Xiuliang; Yang, Ronggui
Abstract: Spray cooling has become one of the most promising heat dissipation technologies for thermal management of super high heat flux. The traditional strategies to enhance spray cooling have mainly strengthened the forced convection at high spray flow rate, or extended the triple line area for evaporation by micro/nano structure, which is challenging in promoting heat transfer efficiency. In this work, multi-layer copper micromesh is applied to increase the heat transfer proportion of liquid film boiling in spray cooling, which improves onset of nucleate boiling (ONB), and enhances the critical heat flux (CHF) and heat transfer coefficient (HTC) simultaneously. Synergistic effects of micromesh structures (including thickness and spacing width) and spray flow rate on liquid supply and bubble escape are demonstrated: high micromesh thickness, small wire spacing width, and large spray flow rate increasing liquid supply but impeding bubble escape. It is shown that the surface temperature at ONB on multi-layer micromesh has decreased by 16 °C approximately, and #100 4-layer micromesh sample exhibits the best heat transfer performance at 1.14 ml/s with CHF of 605.2 W/cm 2 and maximum HTC of 71.45 kW/(m 2 ·K), which is enhanced by 127.3% and 175.7% compared with flat surface, respectively. Graphical abstract: Image 1 Highlights: Heat transfer enhancement of spray cooling due to liquid film boiling by copper micromesh surface is achieved. Optimization of micromesh thickness and spacing width to increase CHF for spray cooling is comprehensively discussed. Synergistic effects of micromesh structures and spray flow rate on liquid supply and bubble escape are demonstrated.